Fibroblast growth factor-23 and risks of cardiovascular and non-cardiovascular diseases: a meta-analysis - Marthi, A; Donovan, K; Haynes, R; Wheeler, D; Baigent, C; Rooney, C; Landray, M; Moe, S; Yang, J; Yang, J; Holland, L; Giuseppe, R; et al. (American Society of Nephrology, 2018)
Background: Fibroblast growth factor-23 (FGF23) has been associated with an increased risk of cardiovascular disease, but it is uncertain how associations for different types of cardiovascular disease vary by level of kidney function. Methods: We identified prospective studies reporting associations between FGF23 and risk of cardiovascular events. Maximally adjusted risk ratios (RRs) were extracted for each outcome, scaled to a comparison of the top versus bottom third of the baseline FGF23 concentration, and the results aggregated. Results: Depending on assay type used, median study FGF23 concentrations ranged between 43-74 RU/mL and 38-47 pg/mL in 17 ‘general populations’ (i.e. populations unselected for chronic kidney disease [CKD]); between 102-392 RU/mL in 9 populations of patients with CKD not requiring dialysis; and between 79-4212 RU/mL and 2526-5555 pg/mL in 8 dialysis populations. Overall, comparing patients in the top versus bottom third of FGF23 concentration, the summary RRs were 1.33 (95% confidence interval 1.12-1.58) for myocardial infarction, 1.26 (1.13-1.41) for stroke, 1.48 (1.29-1.69) for heart failure, 1.42 (1.27-1.60) for cardiovascular mortality, and 1.70 (1.52-1.91) for all-cause mortality. The summary RR for non-cardiovascular mortality, calculated indirectly, was 1.52 (1.28-1.79). When studies were ordered by the average differences in FGF23 between top and bottom thirds, there was no evidence of trend in the RRs. Conclusion: The presence of an association between higher FGF23 concentration and risk of both cardiovascular (atherosclerotic and non-atherosclerotic) and of non-cardiovascular outcomes, together with the absence of any “exposure-response” relationship suggest that the relationship between FGF23 and risk of cardiovascular disease may be non-causal.